METODE SUPPLY CHAIN OPERATION REFERENCE (SCOR) DALAM MENGUKUR KINERJA RANTAI PASOK - Umari Abdurrahim Abi Anwar; Asni Mustika Rani; Tasya Aspiranti (Universitas PGRI Madiun, 2022)
In increasing competitive advantage at this time, companies must control their supply chain performance to remain optimal. PT. ABCXYZ is a company engaged in the food and beverage industry that produces powdered drinks, the main product produced is ginger powder drink. Analysis of the company's supply chain performance is measured using the Supply Chain Operation Reference (SCOR) method. This research is descriptive quantitative using case study research method. Interviews and direct observations were carried out for actual data collection. The results of measuring the performance of PT. ABCXYZ using the SCOR method is perfect order fulfillment by 88%, order fulfillment cycle time by 8 days, cost of goods sold by 41%, and cash to cash cycle time by 17 days